Transmission network expansion planning with security constraints - Silva, I. D.; Rider, M. J.; Romero, R.; Garcia, A. V.; Murari, C. A. (Institute of Electrical and Electronics Engineers (IEEE), 2005)
A mathematical model and a methodology to solve the transmission network expansion planning problem with security constraints are presented. The methodology allows one to find an optimal and reliable transmission network expansion plan using a DC model to represent the electrical network. The security (n-1) criterion is used. The model presented is solved using a genetic algorithm designed to solve the reliable expansion planning in an efficient way. The results obtained for several known systems from literature show the excellent performance of the proposed methodology. A comparative analysis of the results obtained with the proposed methodology is also presented.